2015
DOI: 10.1111/vde.12203
|View full text |Cite
|
Sign up to set email alerts
|

First report in a dog model of atopic dermatitis: expression patterns of protease‐activated receptor‐2 and thymic stromal lymphopoietin

Abstract: These preliminary findings do not confirm a difference in the amount of expression but rather in its pattern. Studies using PAR-2 or TSLP inhibitors could shed light on their clinical relevance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…One typical signaling pathway involves proteinase-activated receptors (PARs), membrane-spanning G protein-coupled receptors that get activated by the cleavage of an extracellular domain [ 25 ]. Among these, PAR1 and PAR2 have been discovered in various constitutive or transient cells in the epidermis, as well as in the dermis [ 26 ], where downstream signaling leads to the expression of various inflammatory mediators [ 27 ], such as interleukin-6 (IL-6) [ 28 , 29 , 30 , 31 ], interleukin-8 (IL-8) [ 30 , 32 , 33 , 34 , 35 ] and thymic stromal lymphopoietin (TSLP) [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…One typical signaling pathway involves proteinase-activated receptors (PARs), membrane-spanning G protein-coupled receptors that get activated by the cleavage of an extracellular domain [ 25 ]. Among these, PAR1 and PAR2 have been discovered in various constitutive or transient cells in the epidermis, as well as in the dermis [ 26 ], where downstream signaling leads to the expression of various inflammatory mediators [ 27 ], such as interleukin-6 (IL-6) [ 28 , 29 , 30 , 31 ], interleukin-8 (IL-8) [ 30 , 32 , 33 , 34 , 35 ] and thymic stromal lymphopoietin (TSLP) [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…may promote Th2 responses through TLR2‐mediated TSLP production in canine keratinocytes, worsening the allergic inflammation in cAD . Immunohistochemical analyses with human TSLP monoclonal antibody demonstrated that the staining intensity of TSLP did not significantly differ between atopic and normal dogs, although the staining pattern was different . These results suggest that canine TSLP is most likely involved in the pathogenesis of cAD, similar to that in human AD.…”
Section: Keratinocyte‐derived Chemokines and Cytokines That Are Direcmentioning
confidence: 75%
“…Similarly, the transcription level of TSLP was shown to be increased in the skin of dogs with CAD . Furthermore, immunohistochemistry of atopic canine skin following challenge with HDM showed a condensed staining pattern of TSLP in the stratum basale, where Langerhans cells are primarily distributed . These results suggest that TSLP produced by keratinocytes may play an important role in the pathogenesis of CAD.…”
Section: Introductionmentioning
confidence: 75%
“…Through these receptors activated keratinocytes may produce various cytokines and chemokines, which have pro‐inflammatory effects. In dogs, TLR2 and PAR‐2 receptors, activated by components of the cell wall of Gram‐positive bacteria and a protease in HDM allergen, respectively, have been shown to be expressed by keratinocytes . One study has demonstrated that canine keratinocytes activated by a PAR‐2 agonist induced transcription of genes promoting T helper 2 (Th2) responses, such as thymus and activation regulated chemokine (TARC) and granulocyte macrophage colony stimulating factor, suggesting that activation of keratinocytes via receptors associated with innate immunity may promote the allergic inflammation observed in CAD …”
Section: Introductionmentioning
confidence: 99%